GE_GERICHTE P/12698/2016 vom 3. März 2021 - GE Cour de justice (2021)
QUALITÉ POUR AGIR ET RECOURIR;MÉDECIN;MORT;FAUTE PROFESSIONNELLE;EMBRYON;HOMICIDE;CLASSEMENT DE LA PROCÉDURE;LÉSION CORPORELLE | CPP.115; CP.125; CC.31; CPP.318; CP.117; CPP.319; CP.129; CP.125